Responsible tourism as a catalyst for sustainable tourism: Lessons from the United Arab Emirates - Badreddine, Amina; Larbi Cherif, Hadjira; Sabri, Azzeddine (The International tax journal, 2025)
This article highlights the crucial link between responsible and sustainable tourism, emphasizing how responsible practices are integral to destination sustainability. Through a comprehensive literature review, it examines conceptual frameworks, stakeholder roles, and implementation challenges, using the United Arab Emirates as a key case study with initiatives like the "Natural Wonders" ecotourism program and Dubai's Sustainable Tourism Initiative. Findings reveal that responsible tourism operationalizes sustainable development principles through four pillars: economic, social, cultural, and environmental responsibility. The research underscores the importance of stakeholder collaboration, tourist education, and digital marketing in enhancing sustainable outcomes. The UAE experience showcases both effective strategies and challenges, such as reconciling luxury tourism with sustainability, managing desert resource constraints, and addressing cultural sensitivities. Ultimately, the study asserts that responsible tourism offers a practical framework for advancing sustainable tourism development when tailored to local contexts and accompanied by strong policy support.